2020
DOI: 10.3390/ani10040743
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Behind-The-Scenes Encounters and Interactive Presentations on the Welfare of Captive Servals (Leptailurus serval)

Abstract: The serval (Leptailurus serval) is a small African felid that is well represented in zoos and often serves as an animal ambassador in encounter programs with zoo visitors. The impact on serval welfare in relation to such programs has not been investigated to date, and the aim of this study was to assess short-term welfare effects of varying levels of visitor interaction in two captive servals. Weekly blocks of four different treatments were imposed three times on each animal over 12 weeks, and the treatments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…When orangutans were given a preference test, they did not show aversion to the public viewing area [ 56 ]. When treatments were applied that varied in the extent of interactions that servals ( Leptailurus serval ) had with zoo visitors, the overall decrease in stereotypic pacing led to the conclusion that some visitor-encounter programs may have a short-term positive benefit for the animals [ 57 ]. Furthermore, the relationship between variables (e.g., visitor abundance, zoo animal behavior) is not necessarily causal: an increase in certain behaviors may attract zoo visitors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…When orangutans were given a preference test, they did not show aversion to the public viewing area [ 56 ]. When treatments were applied that varied in the extent of interactions that servals ( Leptailurus serval ) had with zoo visitors, the overall decrease in stereotypic pacing led to the conclusion that some visitor-encounter programs may have a short-term positive benefit for the animals [ 57 ]. Furthermore, the relationship between variables (e.g., visitor abundance, zoo animal behavior) is not necessarily causal: an increase in certain behaviors may attract zoo visitors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The doctoral theses went into substantially more detail than any of the published literature, typically investigating a larger sample, considering multiple, separate investigations to evaluate welfare or education [32,33,37] or making detailed observations over an extended time period [34]. Parts of these doctoral theses have been published and have been considered in the main analysis [38,42,52]; these aspects were, therefore, excluded from our analysis of the 'other' literature.…”
Section: Types Of Encountersmentioning
confidence: 99%
“…Of the 13 peer-reviewed welfare studies, nine used behavioural observations and five tested physiological measures (Table 3). Four peer-reviewed studies used combined physiological and behavioural measures of welfare [28,29,38,52]. All of the four welfare-focused 'other' studies reported mixed welfare impacts.…”
Section: Welfarementioning
confidence: 99%
See 2 more Smart Citations